EDUKASI KESEHATAN GIGI DAN FISSURE SEALINGSEBAGAI UPAYA PENCEGAHAN KARIES GIGI PERMANEN PADA ANAK SEKOLAH DASAR - Eluama, Merniwati Sherly; Giri, Eli Alexander; Kanaf, Elsaday; Pay, Mery Novaria; Manu, Apri Adiari (MAJU : Indonesian Journal of Community Empowerment, 2025)
The most susceptible tooth surface to caries in children is the occlusal surface of the first and second permanent molars. A program that can be carried out effectively to reduce the risk of caries on the pit and fissure tooth surface is through pit and fissure sealant treatment. The method of community service activities is: education about dental health accompanied by a demonstration of how to brush teeth and fissure sealant filling according to the indications for children who are willing to undergo dental treatment. Results: after dental health education was carried out, there was a significant increase in the good knowledge category, which increased to 55.9%. The percentage of respondents with sufficient knowledge decreased to 44.1% and there were no more respondents included in the poor knowledge category (0%). Fissure sealant filling has been successfully carried out with a target of 30 children, where 38 teeth with deep fissures have been treated. Conclusion: dental health education can increase respondent knowledge. Fissure sealing is one form of effective preventive intervention on permanent first molars because they are the earliest teeth to erupt and are most susceptible to caries, so they are the main target in prevention programs. The combination of educational interventions and preventive clinical actions such as fissure sealing has proven effective in promoting and preventing dental and oral health.